BELAJAR SAMBIL BERMAIN DI MASA PANDEMI MELALUI MEDIA LOOSE PART DI TK SHANTI KUMARA DENPASAR BARAT KOTA DENPASAR - Putri Ida Ayu Ketut; Seriadi Si Luh Nyoman; Luwih I Made (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
Early childhood education is the first and foremost education so learning must also be considered because the most rapid stage of development is at an early age. Education at an early age is certainly different from education at other levels, so learning must be done as interesting as possible. Interesting learning will foster your interest in learning. Learning at an early age is done through play activities. Children as blank papers must of course be given learning with the help of the media. One of the media that can be used during this pandemic is freelance media. Loose part media is learning that invites children to work with a variety of materials that are around the child. The theories used to analyze the problem are Montessori learning theory, constructivism theory and behaviorism theory. This study uses a qualitative research type. The research subjects used were classroom teachers, students and parents at Shanti Kumara Kindergarten Denpasar. Data collection methods are non-participant observation, structured interviews, document studies and literature studies. Data analysis methods used are data reduction, data classification and data presentation. The results showed that the learning process in the midst of the COVID-19 pandemic was carried out at Shanti Kumara Kindergarten Denpasar which was carried out through three stages consisting of the planning stage, the implementation stage and the evaluation stage. Learning through playing during a pandemic with the media also encountered obstacles such as the lack of understanding of parents using zoom, economic difficulties in the midst of a busy parental pandemic, and changes in children's moods. The solution to overcome these obstacles is to socialize about the zoom application, visit children's homes, evaluate with parents and conduct interesting and changing learning.